IMPROVING THE MANAGEMENT OF THE USE OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF SCIENCE TEACHING METHODOLOGY IN MODERN EDUCATION (IN THE RANGE OF PRIMARY GRADES). - Kaypova Gulnara Muratbaevna (Prospects for innovative technologies in science and education, 2026)
This article analyzes the issues of managing the use of artificial intelligence technologies in the process of developing the methodology of teaching subjects in primary grades. The main goal of the study is to scientifically substantiate the methodological and management mechanisms for introducing artificial intelligence tools into the educational process. The research used literature analysis, pedagogical observation and comparison methods. The results showed that the effective management of artificial intelligence increases the quality of education and the cognitive activity of students.